2008
DOI: 10.1590/s1516-35982008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Triptofano na alimentação de codornas japonesas nas fases de recria e postura

Abstract: RESUMO -Objetivou-se estudar o efeito de diferentes planos alimentares, de acordo com os níveis de triptofano, sobre o desempenho e estresse (pela avaliação de parâmetros fisiológicos) de codornas japonesas (Coturnix coturnix japonica) nas fases de recria e postura. Cento e noventa e duas codornas japonesas na fase de recria (30 a 44 dias de idade) foram alojadas em gaiolas e distribuídas em um delineamento em blocos casualizados, com quatro planos de nutrição [0,27 (controle); 0,52; 0,77 ou 1,02% de triptofan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
2
2
0
4
Order By: Relevance
“…Rizzo et al (2008), evaluating the levels of digestible tryptophan (0.27 to 1.02%) in Japanese quails in the growth phase (30 to 44 days old), reported no significant effects on performance, which is in agreement with the present study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Rizzo et al (2008), evaluating the levels of digestible tryptophan (0.27 to 1.02%) in Japanese quails in the growth phase (30 to 44 days old), reported no significant effects on performance, which is in agreement with the present study.…”
Section: Resultssupporting
confidence: 92%
“…Some studies have reported that supplementation of some essential and non-essential amino acids such as glutamine and threonine improve the development and integrity of the intestinal flora, improving the performance of the birds, but no studies were not found in the literature reporting that these changes were promoted by digestible tryptophan in the diets. Different results were reported by Rizzo et al (2008), which showed no effect on any performance variable on different levels of tryptophan to Japanese quails on growth (0.27 to 1.02%) and laying (0.23 to 0.98%). The authors concluded that diets containing same amount of protein and energy could be used 0.27 for growing phase and 0.23% of tryptophan for laying stage.…”
Section: Resultsmentioning
confidence: 60%
“…Results of feed intake, feed conversion (intake/kg of eggs) and viability were in agreement with Rizzo et al (2008), who did not observe any significant differences of these parameters in quails fed diets with increasing dosages of tryptophan, an essential amino-acid precursor for the neurotransmitter serotonin. Neither did Guarini et al (2007) observe effect on the performance of quails fed diets supplemented with kava-kava (Piper methysticum) dry extract, a phytotherapic with anxiolytic/sedative function.…”
Section: Resultssupporting
confidence: 88%
“…In Brazil, the production of quails, especially those destined for egg production, showed a significant increase, associated with the production of laying hens or on small farms as an alternative activity (Rizzo, Guandolini, & Amoroso, 2008). The reason for this success is explained by the quality and high nutritional value of the eggs, which has resulted in widespread acceptance in the consumer market.…”
Section: Introductionmentioning
confidence: 99%